2011 Third International Workshop on Near Field Communication 2011
DOI: 10.1109/nfc.2011.10
|View full text |Cite
|
Sign up to set email alerts
|

inSERT -- An NFC-based Self Reporting Questionnaire for Patients with Impaired Fine Motor Skills

Abstract: Self-reporting patient data are valuable feedback for medical treatment and care process, as well as for clinical trial studies and support of medical treatment. However, traditional paper-based medical patient longitudinal surveys or questionnaires for health and well-being status information are time-and cost-consuming, and may suffer from low patient compliance. Consequently, an NFC-based electronic data capture prototype called inSERT has been designed that allows quick and easy self-reporting for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Background information on the problem was obtained through a review of relevant literature, case studies, interviews, questionnaires, observations and document analyses [41]. Based on the findings from the analyses and our design goals, we developed a design concept and a low fidelity prototype which was then evaluated in focus groups as well as in workshops [28]. We then developed a fully functional proofof-concept prototype which was tested in a long-term field study in a German hospital.…”
Section: Research Approachmentioning
confidence: 99%
“…Background information on the problem was obtained through a review of relevant literature, case studies, interviews, questionnaires, observations and document analyses [41]. Based on the findings from the analyses and our design goals, we developed a design concept and a low fidelity prototype which was then evaluated in focus groups as well as in workshops [28]. We then developed a fully functional proofof-concept prototype which was tested in a long-term field study in a German hospital.…”
Section: Research Approachmentioning
confidence: 99%
“…[22] provide a process to monitor heart-failure patients using NFC technology. Hndreas et.al designed a system by which patients with impaired fine motor skills can input data by their own easily [23]. In [24] the authors modeled a system that takes data from wireless sensors from the patient's body and transmits the data to any android smart phone using NFC technology.…”
Section: Current Technologymentioning
confidence: 99%
“…On the contrary, researches show that the tapping capability declines later than other motor skills [6]. Previous works, such as the relevant papers by Prinz et al [7] and Isomursu et al [8], already showed the feasibility of NFCbased interaction for elderly or patients affected by impaired fine motor skills, despite the inherent complexity related to a huge variability in needs, requirements, and available residual capabilities. The design proposed for the Smart Panel described in the following sections makes it possible to implement it in different shapes, formats, and materials, thus giving the possibility to select the most suitable options according to older users' needs.…”
Section: Advances In Human-computer Interactionmentioning
confidence: 99%